Analisi Potensi Dan Prospek Wisata Halal Dengan Kerangka 6A Di Desa Pematang Johar Kabupaten Deli Serdang - Fanny, Fanny; Arif, Muhammad; Aslami, Nuri (Universitas Labuhanbatu, 2023)
This study aims to analyze the potential and prospects of tourism with framework 6A in pematang johar village, deli serdang regency. This study uses descriptive qualitative methods with data collection techniques, namely observation, interviews, documentation and literature. Based on the results of research Tourism Village pematang johar Deli serdang district has the potential and prospects to go to the halal tourism area. The development of tourism potential of pematang johar village, deli serdang regency with 6A framework has not been optimal. Constraints in the development of tourism potential of pematang johar village deli serdang regency is the lack of budget funds to develop and improve existing facilities and infrastructure. There is social jealousy among the people and the lack of community participation in the development of this tourism.